Development in The Regional Border of Morotai Island 2018 - Fandi Hi. Latief; Parto Sumtaki (Peneliti.net, 2020)
This study aims to closely observe the facts of development in the border area by using the Qualitative Descriptive method. Research results show that in the development development in Morotai there are still limitations, including, the level of poverty that is fluctuating every year, and the Human Development Index (HDI) which is only expected. In addition, economic aspects are also a frightening specter for development in Morotai Island Regency. Spatial planning is not yet pro-people, pro-poor, and pro-border in the front yard. As a result, the economic conditions at the border as reflected today, such as the very lack of economic infrastructure (both transportation, communication, information, and banking) as well as the inconsistency of urbanization of the existing population of the city center of the island of morotai island to isolated villages. the weak technical institutions of the government contributed to the development inconsistency in Morotai. The conclusion of this study is that Morotai as a border area in the aspect of Development is considered to be less than optimal, this is due to the weak role of the BPPD / Morotai Regency Government for the planned program, both from the aspect of Human Resource Development, Infrastructure and other aspects, whereas in the RPJMN, the border area is the homepage The development of the Republic of Indonesia, which must be encouraged, is not the case, so Morotai's IKM and HDI are fluctuating every year until 2018